2019
DOI: 10.7759/cureus.4633
|View full text |Cite
|
Sign up to set email alerts
|

Resident Perspective on Feedback and Barriers for Use as an Educational Tool

Abstract: Background Feedback in physician graduate medical education is not clearly defined. Some parties may view questioning as a form of feedback, others the conversations over lunch, some the comments in the operating room (OR), and still others the written evaluation at planned meetings. The lack of clarity in defining what constitutes feedback is concerning when this is considered a fundamental means of education to enhance practices and care for patients. If residents do not recognize they are receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
(15 reference statements)
0
12
0
3
Order By: Relevance
“…Previous authors have shown that higher trainee satisfaction with feedback may not relate to the actual quality of feedback (Boehler et al, 2006). Additionally, there are well-reported discrepancies between resident and attending perceptions of feedback in terms of quality, frequency, or duration (Sender Liberman et al, 2005;Carr et al, 2018;Albano et al, 2019). As suggested by this study, the implementation of a standardized feedback system like the 3 C's may not immediately improve these issues.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous authors have shown that higher trainee satisfaction with feedback may not relate to the actual quality of feedback (Boehler et al, 2006). Additionally, there are well-reported discrepancies between resident and attending perceptions of feedback in terms of quality, frequency, or duration (Sender Liberman et al, 2005;Carr et al, 2018;Albano et al, 2019). As suggested by this study, the implementation of a standardized feedback system like the 3 C's may not immediately improve these issues.…”
Section: Discussionmentioning
confidence: 64%
“…Previous approaches to address formative feedback during residency training have utilized the implementation of standardized feedback systems (Peccoralo et al, 2012;Wilkinson et al, 2013). These systems can include faculty development (Wilkinson et al, 2013), conversation guides (Peccoralo et al, 2012), or standardized templates (Peccoralo et al, 2012;Hoon et al, 2015;Albano et al, 2019). There is growing evidence that these methods may improve trainee performance, but their implementation is not well studied (Veloski et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…28,43 Evidence that Milestones and entrustable professional activities (EPAs) provide mental models shared between assessors and learners is mixed. 33,[44][45][46][47][48][49] Part of the challenge is structural: Milestones and EPAs that are broadly defined are susceptible to variable interpretation. 49,50 This variability is affected by the larger challenge of the lack of an SMM of any instrument of assessment and the consequences of that assessment, which involves a process akin to negotiation.…”
Section: Challengesmentioning
confidence: 99%
“…Feedback -ou devolutiva -pode ser definido como a transferência de dados observados pelos preceptores durante a prática médica, de modo a contextualizar o saber cognitivo, a habilidade prática e a tomada de decisão, e verificar se os objetivos do aprendizado foram atingidos, visando a uma reflexão do estudante para que ele reconstrua seus conhecimentos e altere seu modo de agir, com o propósito de melhorar sua performance para que atinja as competências necessárias à profissão em prol do paciente 8 . As devolutivas são importantes para os estudantes refletirem sobre a própria performance e o desempenho desejado, de modo que possam buscar suporte para a melhoria de suas desenvolturas em ambientes de prática.…”
Section: Introductionunclassified
“…Para as devolutivas serem efetivas, é necessário que haja entrosamento entre o professor e o aluno, clareza na transmissão, entendimento do discente e identificação dos objetivos do aprendizado desejados tanto pelo estudante quanto pelo preceptor 8 . Além disso, influenciam na efetividade da devolutiva o tempo destinado à observação, o local em que o feedback é realizado e o conteúdo e a forma de transmissão dele 10 .…”
Section: Introductionunclassified